2011
DOI: 10.1007/s11427-011-4249-8
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in neural cell development and brain diseases

Abstract: MicroRNAs play important roles in post-transcriptional regulation of gene expression by inhibiting protein translation and/or promoting mRNA degradation. Importantly, biogenesis of microRNAs displays specific temporal and spatial profiles in distinct cell and tissue types and hence affects a broad spectrum of biological functions in normal cell growth and tumor development. Recent discoveries have revealed sophisticated mechanisms that control microRNA production and homeostasis in response to developmental an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
33
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 128 publications
0
33
0
1
Order By: Relevance
“…This binding impairs translation and inhibits the expression of target genes in a small interfering RNA (siRNA)-like manner [1618]. miRNAs are involved in regulating a broad range of biological processes [19][20][21][22][23][24][25], such as signal transduction pathways that are often dysregulated in cancers [2629].…”
mentioning
confidence: 99%
“…This binding impairs translation and inhibits the expression of target genes in a small interfering RNA (siRNA)-like manner [1618]. miRNAs are involved in regulating a broad range of biological processes [19][20][21][22][23][24][25], such as signal transduction pathways that are often dysregulated in cancers [2629].…”
mentioning
confidence: 99%
“…Chen R et al identified miR-199a as a regulator of IKK which is a major factor promoting a functional TLR-MyD88-NF-B pathway to constitutively secrete proinflammatory/protumor cytokines [39]. A link between dysregulation of miRNAs and human brain disorders has become increasingly evident [40,41]. Recently, extracellular let-7 has been shown to activate the RNA-sensing TLR7 and induce neurodegeneration [42].…”
Section: Regulation Of Tlr Pathways By Mirnasmentioning
confidence: 99%
“…Dysregulation of miRNA expression has been described in several human neurodevelopmental diseases (Martino et al 2009;Xu et al 2010;Feng and Feng 2011;Nowak and Michlewski 2013). For example, Xu et al (2008) demonstrated that miR124a ectopic expression decreases dendritic branching, an effect rescued by the loss of dFMRP expression.…”
mentioning
confidence: 98%
“…An important second way by which miRNAs may alter adult learning and memory is through neurodevelopmental roles (Xu et al 2010;Im and Kenny 2012;Saab and Mansuy 2014). Dysregulation of miRNA expression has been described in several human neurodevelopmental diseases (Martino et al 2009;Xu et al 2010;Feng and Feng 2011;Nowak and Michlewski 2013). For example, Xu et al (2008) demonstrated that miR124a ectopic expression decreases dendritic branching, an effect rescued by the loss of dFMRP expression.…”
mentioning
confidence: 99%